Protective Role of Lycopene Against Oxidative Stress in Liver - Şahin, Kazım; Gencoglu, Hasan; Bilir, Birdal; Küçük, Ömer (Elsevier, 2018)
In this chapter, the role of lycopene in protecting the liver against oxidative stress-induced damage has been discussed. Lycopene, which is a very potent antioxidant, provides defense against cellular damage caused by reactive oxygen species (ROS). Both conjugated and nonconjugated double bonds of lycopene make it highly reactive against oxidative stress-induced damage. A lycopene-rich diet is recommended for patients with liver diseases because numerous epidemiological studies have validated the protective effects of lycopene on the liver. Lycopene has been reported to exert its effects through pleiotropic molecular mechanisms, including transcriptional regulation, cell cycle control, apoptosis, hormonal balance, inflammation, angiogenesis, and metastasis. Molecular studies have indicated that lycopene modulates cellular processes by acting on molecular targets, such as NF-?B (nuclear factor-kappa B), Nrf2 (nuclear factor erythroid 2-related factor 2), PI3K/AKT (phosphoinositide 3-kinase/AKT), VEGF (vascular endothelial growth factor), ROS-producing enzymes (CYP-P450 enzymes, NADPH oxidase, iNOS, COX-2, and 5-LOX), leading to inhibition of liver diseases, including nonalcoholic fatty liver disease (NAFLD) and liver cancer. Here, we summarize the recent data from in vitro and in vivo studies as well as clinical trials to assess the protective effects of lycopene on oxidative stress in liver. © 2018 Elsevier Inc. All rights reserved.
Keywords: Antioxidants; Cancer; Liver; Lycopene; Oxidative stress